Pearlite formation via martensite. (1st June 2022) - Li, Songjie; He, Mengyuan; Hu, Guanjie; Tian, Yun; Wang, Chengduo; Jing, Ben; Ping, Dehai
Abstract: When the coarsening of a second–phase particle in a solid–phase matrix is discussed, the microstructural evolution of the corresponding matrix phase is often unconsciously ignored. Present electron microscope observations have revealed that as–quenched high–carbon Fe–C martensite with a high density of twins first transforms into a pearlite structure upon tempering, followed by shrinkage of the cementite layers, in which ultra–fine θ–Fe3 C particles are connected from a two–dimensional view. Two cementite layers form a loop or necklace–like morphology. Loop shrinkage or aggregation of the ultra–fine carbide particles results in carbide coarsening and pearlite structure development. The driving force for the aggregation of the fine carbide particles or the shrinkage of the cementite layers is believed to be the recrystallization of numerous α–Fe crystallites formed during the martensitic transformation. The thicker cementite layer in the pearlite structure is formed via a similar process (two or more cementite layers merging together) of detwinning behavior. The present experimental observations have revealed a new coarsening mechanism of cementite particles in carbon steels. A new mechanism for pearlite structure formation (twinned martensite can be treated as a precursor of pearlite) and coarsening has also been discussed.